ADVANTAGES OF ASYNCHRONOUS LEARNING IN MODERN CONDITIONS IN UKRAINE - Клименко, Наталія (SWorldJournal, 2025)
The article examines the innovative approach of asynchronous learning in university practice. Let's study and understand together how this innovative approach can change the face of modern education and become a key factor in the success of students in hi